A Cooperative Dynamic Cluster in Multitasking Mobile Networks. Issue 4 (2nd October 2017) - Xu, Shufang; Xu, Dazhuan; Mao, Yingchi; Wang, Huibin
Abstract: Cluster as a classical paradigm has been often used in a multitasking mobile network and evolved into a dynamic cluster, which is motivated by the tasks with dynamic scale and nodal locations. An important question is how to synthesize the power of multiply members in a dynamic cluster and enhance the overall performance of the network. The almost universal setting is that most clusters are based on the fully connected network and the same level of tasks. To solve these questions, it should evaluate and develop the cooperation between nodes in a dynamic cluster and further propose a corresponding cooperation model. In this paper, the theoretical analysis and the basic models of cluster and dynamic cluster are introduced at first. Then an improved cooperation model of a dynamic cluster is proposed in multitasking mobile networks, which is named, cooperative dynamic cluster. As the main elements of the proposed model, the network connectivity and task priorities are also considered and discussed. Finally, a cooperative message forwarding mechanism is established to settle the cluster, the scales of which should be bounded at a reasonable level in view of a time cost. Simulation results demonstrate the efficiency of our proposed cooperative model was higher than the general dynamic cluster and normal method without cluster, respectively about 14% and 66% higher.